A luta pela terra a partir de narrativas de trabalhadores: os posseiros e a revolta da Gleba Silva Jardim-PR (1961) - Andrade, Franciele Margarida Bard (2017)
The present work has the purpose of analyzing the experiences of fighting for the land of small squatters, involved, in 1961, in the conflict in Gleba Silva Jardim, then Medianeira District and currently located in the municipality of Serranópolis do Iguaçu, approximately 80 kilometers Foz do Iguaçu, in the western region of Paraná, from their narratives in oral interviews, reports of the newspapers "Gazeta do Povo", "Diário do Paraná" and "Folha de Londrina", "Revista Oeste" and the process judicial action for maintenance of tenure and the action to contest the maintenance of tenure. The experiences of the small farm squatters will be problematized in the conflictual and contradictory relations that they lived with the government of the State of Paraná and the colonizing companies, subsidiaries of the colonizer Pinho e Terras. This work aims to investigate how small squatters experienced land disputes and elaborate narratives about such confrontations in the process of occupation, colonization and expansion of private land ownership, as well as their life trajectories, constituting a social identity.